MULHERES PRIVADAS DE LIBERDADE E O PRINCÍPIO DA DIGNIDADE DA PESSOA HUMANA: UMA ANÁLISE SOB A ÓTICA DOS DIREITOS HUMANOS (REMUNOM, 2025)
This article aims to analyze how the Brazilian prison system has violated the right to human dignity of incarcerated women, in light of constitutional principles and international human rights treaties. It highlights the State's omissions regarding gender-specific needs and proposes reflections on the implementation of public policies that ensure respect for women's dignity in prison. The research is based on constitutional provisions, international treaties ratified by Brazil, such as the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) and the Bangkok Rules, as well as the principle of human dignity. Through the analysis of the female prison system, the study reveals the public authorities' negligence in ensuring adequate health, hygiene, maternity, and social reintegration conditions for incarcerated women, thereby perpetuating historical inequalities. It concludes that the realization of the rights of incarcerated women depends on the State’s commitment to gender-sensitive public policies that ensure not only the enforcement of the sentence but also the preservation of human dignity.